2018
DOI: 10.1177/1073191118792089
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of In-Person and Cyber Aggression and Victimization, Substance Use, and Delinquent Behavior During Early Adolescence

Abstract: This study evaluated the Problem Behavior Frequency Scale-Adolescent Report (PBFS-AR), a measure designed to assess adolescents' frequency of victimization, aggression, substance use, and delinquent behavior. Participants were 1,263 students (50% female; 78% African American, 18% Latino) from three urban middle schools in the United States. Confirmatory factor analyses of competing models of the structure of the PBFS-AR supported a model that differentiated among three forms of aggression (in-person physical, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 45 publications
1
45
0
2
Order By: Relevance
“…Previous studies have found support for the structure of the PBFS‐AR, measurement invariance across gender, grade, and settings, and concurrent validity with self‐report and teacher report on related measures of beliefs, peer associations, and problem behaviors (Farrell, Sullivan, Goncy, & Le, 2016; Farrell, Thompson, et al, 2018). We followed the recommended system for scoring the measure (Farrell, Thompson, et al, 2018), which involved taking the mean across items after combining the three highest categories on the 6‐point scale, and log transforming the resulting scores to reduce their skewness and kurtosis. Alpha coefficients for physical aggression and victimization were .84 and .91, respectively.…”
Section: Methodsmentioning
confidence: 94%
See 1 more Smart Citation
“…Previous studies have found support for the structure of the PBFS‐AR, measurement invariance across gender, grade, and settings, and concurrent validity with self‐report and teacher report on related measures of beliefs, peer associations, and problem behaviors (Farrell, Sullivan, Goncy, & Le, 2016; Farrell, Thompson, et al, 2018). We followed the recommended system for scoring the measure (Farrell, Thompson, et al, 2018), which involved taking the mean across items after combining the three highest categories on the 6‐point scale, and log transforming the resulting scores to reduce their skewness and kurtosis. Alpha coefficients for physical aggression and victimization were .84 and .91, respectively.…”
Section: Methodsmentioning
confidence: 94%
“…The Problem Behavior Frequency Scale—Adolescent Report Version 2 (PBFS‐AR; Farrell, Thompson, Mehari, Sullivan, & Goncy, 2018) measures adolescents’ frequency of aggression, victimization, and other problem behaviors. The current study focused on the 5‐item physical aggression scale and the 15‐item in‐person victimization scale.…”
Section: Methodsmentioning
confidence: 99%
“…This study used the Physical Aggression subscale, which consisted of five items (e.g., “Hit or slapped someone” and “Thrown something at someone to hurt them”). The total score was based on the mean after combining responses in the three highest categories based on prior IRT analyses (Farrell, Thompson, Mehari, Sullivan, & Goncy, ) and calculating the mean across items. Alpha coefficients ranged from .76 to .82 across waves.…”
Section: Methodsmentioning
confidence: 99%
“…Farrell et al () found support for strong measurement invariance across gender, location, and time, as well as support for construct validity of the PBFS‐AR using measures of related constructs based on teacher‐ and student‐report. We calculated the total score by combining the three highest categories based on prior analyses using item response theory (Farrell, Thompson et al, ), and calculating the mean across items. α Coefficients ranged from 0.76 to 0.82 across waves.…”
Section: Methodsmentioning
confidence: 99%
“…The frequency of engaging in physical aggression was assessed by the Problem Behavior Frequency Scale-Adolescent Report (PBFS-AR; Farrell, Sullivan, Goncy, & Le, 2016;Farrell, Thompson, Mehari, Sullivan, & Goncy, 2018). Physical aggression toward others was measured using five items (e.g., "hit or slapped someone" and "threatened someone with a weapon [gun, knife, club, etc.]").…”
Section: Physical Aggressionmentioning
confidence: 99%